Effect of Red Dragon Fruit Extract Ingestion on Mitochondrial Cytochrome c Levels in Rat Soleus Muscle Following Moderate Exercise - Ade Indra Mukti; Gusbakti Gusbakti; Putri Handayani; Dewi Sartika; Alvin Abrar Harahap; Sulaiman Delrizal (Althea Medical Journal, 2026)
Background: Exercise-induced free radicals harm cellular mitochondria and trigger apoptosis via cytochrome-c release. Red dragon fruit (RDF) extract is known for its potent antioxidant properties. This study aimed to investigate whether RDF extract could counteract oxidative stress and apoptosis in rat soleus muscle post-exercise.Methods: This experimental study employed a randomized posttest-only control group design, conducted at the Animal House Unit of the Biology Laboratory, Universitas Sumatera Utara. Using 25 male rats, approximately 3 months old and weighing 200 g, selected by simple random sampling. Subjects were divided into five groups: sedentary control (K1), exercise-only (K2), and three test groups receiving RDF extract (75, 150, and 300 mg/kg) alongside moderate-intensity swimming for 31 days. Measured variables included malondialdehyde (MDA), cytochrome-c, and muscle histology. Data were analyzed using Kruskal-Wallis and Mann-Whitney tests (p<0.05).Results: RDF-treated rats showed significantly lower levels of MDA and cytochrome-c compared to the exercise-only group. The Kruskal-Wallis test revealed significant differences among groups for both MDA (p=0.002) and cytochrome-c (p=0.003). Post-hoc analysis showed that the exercise-only group (K2) exhibited the highest cytochrome-c levels (mean rank 16.50), whereas the highest RDF dose (300 mg/kg) significantly reduced it (mean rank 6.75, p=0.008 vs. K2). Histopathological analysis confirmed less muscle tissue damage and reduced inflammatory cell infiltration in extract-treated groups.Conclusions: RDF extract suppresses exercise-induced oxidative stress, inhibits apoptotic signaling, and protects muscle tissue, demonstrating its potential as a post-exercise recovery supplement.